Światowe reperkusje badań PISA. Wokół nowej kontroli edukacji - Brudzińska, Patrycja (Studia Edukacyjne, 2018)
The paper presents the reactions of societies to the results of the Program for International Students Assessments (PISA) and some of the effects of this research. It presents education reforms and changes in education systems introduced as a consequence of confrontation of results achieved by fifteen-year-olds from different countries. The text describes examples of participants from Europe, America and Asia.